IMPLEMENTASI PROGRAM POSBINDU PENYAKIT TIDAK MENULAR - Fitriyani, Dian; Dewi, Siti Utami; Wirawan, Susilo; Kartadarma, Supriyatni; Purnomo, Heru (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Deaths from non-communicable diseases are expected to continue to increase worldwide. More than two thirds (70%) of the global population will die from non-communicable diseases such as cancer, heart disease, stroke and diabetes. In total, it is predicted that by 2030 there will be 52 million deaths per year due to non-communicable diseases, an increase of 9 million from 38 million at present. Lubuk Ambacang is one of the community health center in Kuantan Singingi Regency which in the last 3 years has increased hypertension to 59.2%, and diabetes mellitus to 21.5%. According to the Indonesian Ministry of Health in the Technical Guidelines for the Implementation of Non-Communicable Diseases, one of them is the implementation of PTM Posbindu. The purpose of the study was to find out the implementation of the Posbindu Program for Non-Communicable Diseases in the Work Area of the Lubuk Ambacang community health center, Kuantan Singingi Regency in 2021. The study used qualitative analytical methods conducted the Lubuk Ambacang community health center, Kuantan Singingi Regency used 7 informants. The results showed that in general the implementation of Posbindu PTM in Lubuk Ambacang community health center has been running, but there are several obstacles such as Human Resources not in accordance with SOPs or PTM implementation guidelines according to the Indonesian Ministry of Health, Limited availability of funds, availability of infrastructure that does not meet the 100% requirements and community support that has not been maximized. It is suggested to Lubuk Ambacang community health center to increase the type of PTM Posbindu from the basic PTM Posbindu to the main PTM Posbindu so that people are more enthusiastic about utilizing the PTM Posbindu.Keywords: Implementation, Posbindu, Hypertension, Human Resources